(untitled) (International Journal of Engineering and Computer Science, 2015)
Protecting information in potentially averse environments – is a crucial factor in the growth of information-based processes in industries, business, and administration as information is the most important asset of an organization. Cryptography is basically practice and study of techniques for secure communication in the presence of third parties (called adversaries). The Advanced Encryption Standard (AES) specifies a FIPS-approved cryptographic algorithm that can be used to protect electronic data. The AES algorithm is a symmetric block cipher that can encrypt (encipher) and decrypt (decipher) information. Like DES, AES is a symmetric block cipher. However AES is different from DES in a number of ways. The algorithm Rijndael allows for a variety of block and key sizes. It is capable of using cryptographic keys of 128, 192, and 256 bits to encrypt and decrypt data in blocks of 128 bits. This review paper concentrates on framing together efficient implementation of AES algorithms in number of fields. The study also focus on number of ways to expedite the encryption process by using different approaches.